Refractory Severe Thrombocytopenia during Pregnancy: How to Manage - Amorim, Joana Gomes de; Abecasis, Manuel Rocha; Rodrigues, Filipa Maria Nogueira Lança (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Thrombocytopenia is the most common hemostatic change in pregnancy, but severe thrombocytopenia is rare. One of the causes, immune thrombocytopenic purpura (ITP), is characterized by increased platelet destruction by immunoglobulin G (IgG) antibodies, presenting a high risk of hemorrhage for the patient, but also for the fetus, since antibodies may cross the placenta. We present the case of a 23-year-old pregnant woman with a history of Langerhans cell histiocytosis of the mandible submitted to surgery and chemotherapy when she was 10 years old, with diagnosis of ITP since then. At 28 weeks of gestation, she presented with petechiae, epistaxis, and gingival bleeding, with a platelet count of 3 × 109/L and positive IgG antiplatelet antibodies test. At a multidisciplinary discussion, it was decided to delay a cesarean section, due to the absence of fetal distress and to the high risk of morbidity for the patient. Many therapies were attempted without success. The IgG produced a slight and transient increase in the platelet count. On the 36th week of gestation, an elective cesarean section was performed. The perioperative period transfusions were guided by rotational thromboelastometry (ROTEM) monitoring. The procedure was performed under general anesthesia and videolaryngoscopy-assisted intubation. The patient was hemodynamically stable, without significant bleeding, and was transferred to the intensive care unit. The platelet count eventually decreased and a splenectomy was performed. Regional anesthesia may be contraindicated, and general anesthesia is associated with an increased risk of airway hemorrhage due to traumatic injury during the tracheal intubation and of hemorrhage associated with the surgical procedure. A multidisciplinary approach is essential in high-risk cases.
Keywords: pregnant woman; thrombocytopenia; idiopathic thrombocytopenic purpura; thromboelastometry; hemorrhage